The Effect of Online Learning and Learning Motivation During the Covid-19 Pandemic on Student Academic Achievement - Hasanah; Izhari, Fadhilah; Sunarti; Qibtiah, Mariatul; Chaidir, Haikal Abdallah (Global Writing Academica Researching & Publishing, 2024)
The Covid-19 pandemic has changed the process of teaching and learning activities that are carried out offline (offline) to online (online), students must adapt and transform to new habits with online learning methods which are closely related to the existence of an internet network. This study aims to determine and analyze the effect of online learning and learning motivation during the Covid-19 pandemic on the academic achievement of students of the Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Jakarta. The research method used is descriptive method with a survey method with a quantitative approach. Data collection used primary data and secondary data. Population of 1546 active students according to LLDikti data, while samples were taken using the Slovin formula calculation of 341 respondents. The results of this study are that online learning and learning motivation together (simultaneously) have a positive effect on student achievement variables. That is, the better the value of online learning and learning motivation, the greater the achievement of students at the Faculty of Economics and Business at Muhammadiyah University Jakarta